2012
DOI: 10.5897/ajar12.1519
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and economic feasibility of red beetroot (Beta vulgaris L. ssp. vulgaris Rote Kugel) from different production systems

Abstract: The study determined the internal quality (the total phenol, sugar, organic acid contents, antioxidant activity, and mineral components) and physical parameters in the flesh of red beetroots produced in different production systems (conventional, integrated, organic, and control) using established methods. Organic cropping of red beetroot plants significantly reduced the yield by 27% of some macro minerals (P at 23.1, K at 13.1, and Mg at 7.7%) in comparison with conventional cropping but increased the ascorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It was reported that the total polyphenol content of the organic beetroots was significantly higher than the conventional ones, although the difference depended on the cultivar [62]. Nevertheless, the study of Straus et al (2012) demonstrated a higher total phenolic content in beetroots grown under organic condition compared to the conventional ones, however, the difference was not significant [63].…”
Section: Total Phenolic Contentmentioning
confidence: 94%
“…It was reported that the total polyphenol content of the organic beetroots was significantly higher than the conventional ones, although the difference depended on the cultivar [62]. Nevertheless, the study of Straus et al (2012) demonstrated a higher total phenolic content in beetroots grown under organic condition compared to the conventional ones, however, the difference was not significant [63].…”
Section: Total Phenolic Contentmentioning
confidence: 94%
“…The red beet root (Beta vulgaris L.) is a traditional vegetable that is widely consumed in several countries. The caloric value is moderate, but it is a rich source of fiber and sugars (Straus et al, 2012). Consumption of red beet, which is rich in phenolic acids and has high antioxidant capacity, can help protect against age-related diseases (Ravichandran et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Szopinska and Gaweda (2013) found lower C vitamin content in beetroot and its content varied depending on a year and method of cultivation from 5.06 mg/100g to 9.46 mg/100g. Straus et al (2012) reported high levels of vitamin C in beetroot ranging from 23.3 mg/100g to 33.9 mg/100g. Among the analyzed beetroot fresh samples originating from different geographic locations, vitamin C varied but was not statistically significant (LSD test, p < 0.001).…”
Section: Ascorbic Acid (Vitamin C)mentioning
confidence: 99%
“…Demands for organically produced food are high because consumers desire food from reliable sources, grown in environmentally friendly produced conventionally and organically. Many research studies proved that organically produced food products contain more bioactive components (vitamins and phenols), due to the prohibition of the use of synthetic pesticides and fertilizers (Bourn & Prescott 2002;Bavec, Mlakar, Rozman, Pazek & Bavec, 2009;Straus et al 2012;Kazimierczak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%